Vacuum effect of wrongful criminal justice process: The case of Indonesia - Rahmawati, Erni; Dermawan, Mohammad Kemal (Indonesian Journal of Social Science Research, 2023)
Introduction: The victims in Indonesia who have been wrongly arrested in various phases of the criminal justice process and have accordingly experienced suffering are not yet included within the terms. The existing term does not clearly describe the officials responsible for the wrongful arrest while enforcing criminal law either. This study aims to address these problems. Method: Using literature review as a research method to explain problems regarding the terms of wrongful arrest, the study also uses critical victimology, which includes structural victimization and state crime. Results: The process of wrongful arrest in Indonesia comprised of victims who were released in the early phase of the case investigation and victims who have served their sentences. Additionally, officials in the criminal justice system, especially the police, and judges, have a significant role in attracting people into the criminal justice system and keeping them in the position of the perpetrator until the last phase, even when all the evidence point to the victim’s innocence. Conclusions: Such a characteristic can be described as a vacuum. It tends to suck the victims until the final phase despite its ability to release them in the middle of the process with the help of parties of the justice system. Given this problem, wrongful criminal justice process as a new term has emerged, which includes and explains problems not adequately addressed by the previous term. Through this term, it is expected that the victims will get more attention and receive compensation from the state.